Ciências e educação em museus no final do século XIX The sciences and education in museums at the close of the nineteenth century - Maria Margaret Lopes; Sandra Elena Murriello (História, Ciências, Saúde: Manguinhos)
Nas últimas décadas do século XIX, os museus de história natural estabeleceram sólidas redes de comunicação entre si, com seus diferentes públicos conformando o processo internacional caracterizado como o 'movimento dos museus'. Nesse contexto de intercâmbios apresenta-se o discurso que pronunciou William H. Flower, em 1889, sobre os papéis que cabiam aos museus de história natural. Neste trabalho analisa-se a sua influência no recém-inaugurado Museo de La Plata, Argentina, integrante desse circuito de museus que se ampliava no período. In the closing decades of the nineteenth century, natural history museums established solid communication networks, and their different audiences formed what became known as the 'museum movement'. It was within this context of exchange that William H. Flower made his 1889 speech on the roles natural history museums should play. The article analyzes his influence on Argentina's Museo de La Plata, a member of this then-expanding circuit of museums.